Hubungan Motivasi Suami dan Tenaga Kesehatan dengan Kunjungan Ante Natal Care (ANC) pada Ibu Hamil di BPM Ny. H. Pakisaji Kabupaten Malang - Anggrawati Wulandari; Miftakhur Rohmah (Journal for Quality in Women's Health, 2019)
Pregnancy and childbirth complications as the highest cause of maternal death can be prevented by regular antenatal care (ANC) antenatal care. In addition to husband's support, the support of health workers also plays a role in antenatal care visits. The purpose of the study was to determine the relationship between the motivation of husband and health workers with the visit of ante natal care (ANC) to pregnant women in BPM Ny H Pakisaji Malang Regency. The research design used a correlation with a cross sectional approach. The population is all pregnant women of TM III who conduct antenatal care at BPM Ny H Pakisaji, Malang Regency, totaling 26 respondents. The sampling technique uses purposive sampling so that the sample is 26 mothers. Data analysis using logistic regression. The motivation of husbands in pregnant women is almost half, namely 10 respondents (38.5%) with sufficient husband's motivation.